Analisis Ekuitas Merek pada Perusahaan Online - Mahardhika Cipta Raharja (Mabsya: Jurnal Manajemen Bisnis Syariah, 2019)
This study is an empirical study, entitled "Ekuitas Merek pada Perusahaan Online". The purpose of this study was to analyze the measurement model of brand equity in a online company, that if the traditional measurement model that has been used in the offline company applied to the online company.Subjects in this study were users of social networking site Facebook. The object of this study is brand awareness, brand value, brand trust, brand loyalty, and brand equity. Based on the results of research and data analysis with Structural Equation Modeling (SEM) showed that: (1) The level of consumer awareness no positive effect on brand equity from online business brand, (2) The value of the brand is not a positive influence on brand equity from online business brand, (3) Levels consumer trust is not a positive influence on brand equity from online business brand, (4) Positive impact of consumer loyalty to the brand equity of the business brand online, (5) Brand awareness has a positive effect on the value of the brand online business associations, (6) Brand awareness have a positive effect on the association of brand trust in online businesses, (7) The perceived value is not affected positively the trust level of brand in online business; (8) Trust has a positive effect on the level of brand loyalty in business online, and (9) The perceived value has a positive effect on the level of brand loyalty in business online.The implications of the above conclusion that in order to achieve the highest power of a brand, brand equity is measured in the form of an online business, an effort that can be done is to consider each of the dimensions of brand equity, including brand awareness, brand association (in the form of brand value and brand trust), and brand loyalty.